2017
DOI: 10.15761/cmi.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Exploring family needs in neonatal and pediatric intensive care units at King Khaled Hospital- Jeddah

Abstract: Family-centered care (FCC) approach acknowledges that the family has the greatest influence over an infant's / child's health and well-being. Assessing the FMs' needs is an important component to apply and improve family-centered care, and it is essential for pediatric nurses in the intensive care units to identify and understand these needs. Meeting the needs of family having neonate or child in intensive care is part of implementing the philosophy of family-centered care.Aim of the study is to explore nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
3
1
3
Order By: Relevance
“…Coherent with the literature, the results of this study showed that there are similarities and differences in terms of family members and nurses’ perceived need for patient relatives ( Maxwell, Stuenkel & Saylor, 2007 ; Moggai, Biagi & Pompei, 2005 ; Hinkle & Fitzpatrick, 2011 ; Alnajjar & Elarousy, 2017 ). Family scores were higher than those of nurses.…”
Section: Discussioncontrasting
confidence: 46%
“…Coherent with the literature, the results of this study showed that there are similarities and differences in terms of family members and nurses’ perceived need for patient relatives ( Maxwell, Stuenkel & Saylor, 2007 ; Moggai, Biagi & Pompei, 2005 ; Hinkle & Fitzpatrick, 2011 ; Alnajjar & Elarousy, 2017 ). Family scores were higher than those of nurses.…”
Section: Discussioncontrasting
confidence: 46%
“…Coherent with the literature, the results of this study showed that there are similarities and differences in terms of family members and nurses' perceived need for patient relatives. (12,17,18,19). Family scores were higher than those of nurses.…”
Section: Discussionmentioning
confidence: 82%
“…Sosyal destek ve yoğun bakımda çocuğu olan diğer hasta yakınları ile görüşmekte de ailenin kendine gelmesine ve başa çıkmasına yardım etmektedir. Hatta ortam izin verdiği müddetçe gelip çocuğu iletişim kurmalarının sağlanması da ailenin anksiyetesini azaltarak başa çıkmasını kolaylaştırmaktadır (20,21) . Alnajjar ve Elarousy'nin (20) (21) .…”
Section: Ailenin Başa çıKmasının Desteklenmesiunclassified
“…Hatta ortam izin verdiği müddetçe gelip çocuğu iletişim kurmalarının sağlanması da ailenin anksiyetesini azaltarak başa çıkmasını kolaylaştırmaktadır (20,21) . Alnajjar ve Elarousy'nin (20) (21) . Abdel-Latif ve ark.…”
Section: Ailenin Başa çıKmasının Desteklenmesiunclassified